The Embodiment of Folklore Traditions in Art as the Antithesis of Postmodern Aesthetics - Alesia I. Gurchenko (Publishing house "Sreda", 2021)
The aim of the research is to comprehend the folklore traditions embodied in art as an antithesis to the aesthetics of the postmodern era. The author puts forward a hypothesis according to which, against the background of a change in the socio-cultural paradigm from modernity to postmodernism, folklorism acted as a tool for returning to genuine values ​​based on centuries-old authentic traditions. Folklorism is considered in the article as a phenomenon in which the potential of the collective memory of the people is laid, allowing a person to recognize himself as part of a single nation with deep historical roots and centuries-old cultural traditions. Research methods - the comprehension of folklorism as an antithesis in relation to the dominant sociocultural paradigms was carried out using the scientific principle of historicism, as well as the methods of synchronous and diachronous analysis. The results of the research - another surge of interest in authenticity against the background of the approval of postmodern ideas is presented as one of the examples of a cyclical return to true values ​​in art. It is concluded that the analyzed bright and self-sufficient artistic phenomenon, over more than two centuries of its existence, has repeatedly acted as a mechanism to smooth out the existing contradictions in the sociocultural model of the development of society, thereby creating stable axiological foundations in art.